A method for preparing zinc nanowires

The solvent, zinc precursor and catalyst were mixed and heated to decompose it by mixing and heating the solvent, zinc precursor and catalyst, and zinc nanowires with uniform diameter and length were successfully prepared, solving the problem of difficulty in efficient preparation of zinc nanowires in the prior art, and achieving efficient and stable nanowire preparation.

CN119260018BActive Publication Date: 2025-04-29WESTLAKE UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411625861.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-04-29
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

It is difficult to efficiently prepare zinc nanowires with specific morphology and functions in the prior art, and solvothermal method has almost not been reported in the preparation of zinc nanowires.

Method used

By using the solvent heat method, zinc nanowires with a diameter of 20-180 nm and a length of 5-50 μm were prepared by mixing the solvent, zinc precursor and catalyst, and performing a heating and decomposition reaction.

Benefits of technology

The zinc nanowires are prepared stably and efficiently. The nanowires are single crystal structures, uniform in size, length can exceed 20μm, and conversion rate can reach 70%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119260018B_ABST
    Figure CN119260018B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing zinc nanowires, comprising: mixing a solvent, a zinc precursor and an optional surfactant to obtain a solution 1; mixing a solvent and a catalyst to obtain a solution 2; mixing solutions 1 and 2 to obtain a solution 3, and heating to decompose the zinc precursor to obtain zinc nanowires. The method for preparing zinc nanowires according to the present invention is a solvothermal method, which can stably and efficiently prepare zinc nanowires. The synthesized zinc nanowires have uniform size, a length of more than 20 μm, and a single crystal structure, and a conversion rate of up to 70%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of zinc nanomaterials, and specifically relates to a method for preparing zinc nanowires and zinc nanowires prepared thereby. Background Art

[0002] With the development of nanotechnology, metal nanomaterials have been gradually applied to the fields of optics, electricity, energy, etc., and the development of metal nanomaterials with specific morphology and functions has received more and more attention. As one of the members of nanomaterials, nanowires have been favored by researchers in the fields of condensed matter physics, chemistry and materials science due to their excellent optical, electrical, mechanical and catalytic properties, and have become a hot topic in nanomaterial research in recent years.

[0003] Metallic zinc is an important transition metal element, which is mainly used in the fields of metal corrosion protection, batteries, industrial catalysis, organic synthesis, alloys, etc. There are two main methods for preparing zinc nanowires: vapor deposition and electrochemical template method. Among them, vapor deposition for preparing zinc nanowires has high energy consumption, low yield, and difficult to control morphology, and the obtained nanowires are mostly curved. Electrochemical deposition usually requires the use of porous anodized aluminum or etched porous polycarbonate as a template, and zinc nanowires are prepared by electrochemical reduction, and then the template is removed by post-treatment. This strategy can produce straight nanowires, but the diameter and length of the nanowires are limited by the template, and longer nanowires cannot usually be prepared. In addition, this method is inefficient, the template is difficult to remove, and it is time-consuming and laborious. Due to the high activity of metallic zinc itself, it is extremely challenging to synthesize nano-sized metallic zinc compared to other metals. It is difficult to synthesize nano-sized metallic zinc, and it is even more difficult to prepare one-dimensional nanowires that require strict control of morphology.

[0004] Currently, there is no stable and efficient method for preparing nanosized metallic zinc, and there are almost no reports on the solvothermal method for synthesizing metallic zinc nanowires. The solvothermal methods for synthesizing other metal nanowires are mostly carried out in aqueous phase. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing zinc nanowires, which is easy to operate and simple in process, and can stably and efficiently prepare zinc nanowires. The method for preparing zinc nanowires according to the present invention is a solvothermal method, which can stably and efficiently prepare zinc nanowires. The prepared zinc nanowires are single crystal structures, have a diameter of 20-180nm, and a length of 5-50μm, and can be adjusted within a certain range.

[0006] According to one aspect of the present invention, there is provided a method for preparing zinc nanowires, comprising:

[0007] (1) mixing a solvent, a zinc precursor and an optional surfactant to obtain a solution 1;

[0008] (2) mixing a solvent and a catalyst to obtain a solution 2;

[0009] (3) Solutions 1 and 2 are mixed to obtain solution 3, and the solution is heated to decompose the zinc precursor to obtain zinc nanowires.

[0010] Further, the solvent used in the synthesis can be selected from C5-C7 alkanes, C5-C7 cycloalkanes and diethyl ether, such as pentane, hexane, heptane, cyclopentane, cyclohexane, cycloheptane and diethyl ether, especially n-hexane or a combination of n-hexane and diethyl ether. Further, the zinc precursor used in the synthesis can be represented by ZnR 1 2 , where R 1 Independently selected from alkyl groups having a carbon number of 2 or more, preferably C2-C10 alkyl groups, and more preferably C2-C4 alkyl groups. In particular, zinc precursors include but are not limited to diethyl zinc, dipropyl zinc, diisobutyl zinc, and the like. In the case of using the above zinc precursors, zinc nanowires can be obtained smoothly. In the case of not using the above alkyl zinc, such as when using dimethyl zinc, zinc nanowires cannot be obtained. Without being limited to any theory, it is believed that when the carbon number of the alkyl group in the zinc precursor is greater than 2, a β-hydrogen removal reaction can occur to obtain metallic zinc, thereby obtaining zinc nanowires, while dimethyl zinc does not contain β-hydrogen, so that a β-hydrogen removal reaction cannot occur to obtain metallic zinc, and thus zinc nanowires cannot be obtained.

[0011] Furthermore, the catalyst used in the synthesis is a titanium-based catalyst. The titanium-based catalyst can be selected from TiR 2 4 , where R 2 Independently selected from chlorine, bromine, iodine, cyclopentadienyl, C1-C6 alkoxy; or, in particular, the titanium-based catalyst includes but is not limited to titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, di(cyclopentadienyl)titanium dichloride, cyclopentadienyltitanium trichloride, titanium tetraisopropoxide, titanium acetylacetonate, tetrabutyl titanate, etc. One or a combination of two or more. In the case of using a titanium-based catalyst, zinc nanocrystals can be obtained at a lower temperature. In the case of not using a titanium-based catalyst, zinc nanocrystals cannot be obtained at a lower temperature, such as the cracking temperature of diethyl zinc is greater than 300°C.

[0012] Furthermore, the surfactant used in the synthesis is an amine-based surfactant. The amine-based surfactant can be represented by R 3 N(CH 3 ) 2 , where R 3Selected from C4-C20 alkyl. In particular, the amine-based surfactant includes, but is not limited to, one or more of octadecyl dimethyl tertiary amine (full name: octadecyl dimethyl tertiary amine), hexadecyl dimethyl tertiary amine (full name: hexadecyl dimethyl tertiary amine), dodecyl dimethyl tertiary amine (full name: dodecyl dimethyl tertiary amine), N, N-dimethyldecylamine, N, N-dimethylhexylamine, etc. In the case of using the above-mentioned surfactant, it is beneficial to obtain zinc nanowires with uniform morphology and controllable size and reduce irregular particles in the synthetic product. In the case of not using the above-mentioned surfactant, although zinc nanowires can also be obtained, the uniformity of the morphology and size of the obtained zinc nanowires is low, and the number of irregular particles increases.

[0013] Further, in solution 3, the concentration of the zinc precursor is 0.2-2 mol / L, such as 0.2, 0.3, 0.5, 1.0, 1.5, 1.9, 2.0 mol / L, etc., preferably 0.2-1.5 mol / L, in terms of zinc molar concentration. Within the above range, zinc nanowires of uniform size can be obtained, while too low a concentration may increase the proportion of irregular particles.

[0014] Further, in solution 3, the concentration of the catalyst is 0.001-0.1 mol / L, such as 0.002, 0.003, 0.004, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 mol / L, etc., preferably 0.003-0.05 mol / L, in terms of molar concentration of titanium. Within the above range, zinc nanowires of uniform size can be obtained; while if the concentration is too high, irregular particles may be produced; if the concentration is too low, the yield may be reduced, and the proportion of irregular particles may increase.

[0015] Further, in solution 3, the concentration of the surfactant is 0-0.5 mol / L, for example, 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.1, 0.15, 0.20, 0.25, 0.30, 0.40, 0.50 mol / L, etc., preferably 0.1-0.4 mol / L. Within the above range, it is beneficial to obtain zinc nanowires of uniform size. If the concentration is too high, zinc nanoparticles will be obtained, reducing the yield of zinc nanowires.

[0016] Furthermore, in step (3), the molar ratio of zinc precursor to catalyst (Zn / Ti) can be 30-200:1, for example, 30:1, 50:1, 70:1, 90:1, 120:1, 150:1, 200:1, etc., preferably 60-120:1. Within the above range, a product mainly composed of zinc nanowires can be obtained. If the molar ratio is too high, the yield will be reduced; and if the molar ratio is too low, the proportion of irregular particles will increase.

[0017] Furthermore, in step (3), the reaction temperature for the decomposition reaction can be 60-200°C, such as 60, 80, 100, 120, 150, 200°C, etc., preferably 60-150°C. Within the above temperature range, a product mainly composed of zinc nanowires can be obtained. If the temperature is too high, the proportion of irregular particles will increase; and if the temperature is too low, the reaction yield will be reduced.

[0018] Furthermore, in step (3), there is no particular restriction on the reaction time as long as zinc nanowires can be obtained. For example, the reaction time is more than 2 hours, more than 4 hours, for example, 4-48 hours, etc., but is not limited thereto.

[0019] The method for preparing zinc nanowires according to the present invention may further include a conventional purification step. For example, in step (3), the reaction product is filtered to obtain a precipitated product, which is then washed and dried.

[0020] The washing can be performed with a solvent. There is no particular requirement for the washing solvent, as long as it can remove the remaining zinc precursor, titanium-based catalyst, and surfactant. For example, the washing solvent can be one or a combination of two or more of hexane, toluene, tetrahydrofuran, 1,4-dioxane, and isopropanol.

[0021] Drying can be carried out in a nitrogen-protected environment, such as a high-temperature drying oven after nitrogen replacement.

[0022] According to one aspect of the present invention, there is provided a zinc nanowire, which is prepared by the above-mentioned method for preparing the zinc nanowire according to the present invention.

[0023] Furthermore, the zinc nanowire according to the present invention is a single crystal structure, with a diameter of 20-180 nm and a length of 5-50 μm.

[0024] Beneficial Effects

[0025] Compared with the existing methods for preparing zinc nanowires, the solution synthesis method of the present invention is highly efficient and can more easily introduce surfactants for morphology adjustment. The synthesized zinc nanowires are uniform in size, can be more than 20 μm in length, and have a single crystal structure, with a conversion rate of up to 70%. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the SEM image of zinc nanowires synthesized in Example 1.

[0027] Figure 2 This is the XRD pattern of the nanowires synthesized in Example 1.

[0028] Figure 3 This is the SEM image of zinc nanowires synthesized in Example 2.

[0029] Figure 4 This is the SEM image of zinc nanowires synthesized in Example 3.

[0030] Figure 5 This is the SEM image of zinc nanowires synthesized in Example 6.

[0031] Figure 6 This is the diameter distribution diagram of the zinc nanowires synthesized in Example 6.

[0032] Figure 7 The left picture is a TEM image of the zinc nanowires synthesized in Example 6, and the right picture is a selected area electron diffraction image.

[0033] Figure 8 This is the SEM image of zinc nanowires synthesized in Example 7.

[0034] Fig. 9 This is the SEM picture of Comparative Example 1.

[0035] Fig.10 This is the SEM picture of Comparative Example 2. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0037] SEM results were obtained using a scanning electron microscope (Themo Scientific).

[0038] The X-ray diffraction results were measured on a polycrystalline X-ray diffractometer (Bruker).

[0039] TEM results were measured on a transmission electron microscope (Talos F200X G2).

[0040] The conversion rate refers to the conversion rate of the zinc precursor into zinc, which is calculated as the mass percentage of the final solid product (including zinc nanoparticles and zinc nanowires) obtained in the example based on the zinc precursor.

[0041] Example 1

[0042] (1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0043] (2) dissolving titanium tetrachloride in n-hexane solution to prepare a catalyst solution with a concentration of 0.034 mol / L;

[0044] (3) adding the prepared catalyst solution to the zinc precursor solution of step (1), wherein the volume ratio of the precursor solution to the catalyst solution is 2:1, mixing well, and reacting at 90° C. for 48 hours;

[0045] (4) After the reaction is completed, the solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence, and dried under a nitrogen environment to obtain zinc nanowires with a conversion rate of about 30%.

[0046] Figure 1 This is a SEM image of zinc nanowires synthesized in Example 1. Figure 1 As shown, the diameter of the synthesized zinc nanowires is about 50-120 nm and the length is about 30-50 μm.

[0047] The results of polycrystalline X-ray diffraction are shown in Figure 2 , compared with the zinc standard PDF card (PDF 65-3358), it shows that the synthesized nanowires are metallic zinc nanowires.

[0048] Example 2

[0049] (1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0050] (2) dissolving titanium tetrabromide in n-hexane solution to prepare a catalyst solution with a concentration of 0.034 mol / L;

[0051] (3) adding the prepared catalyst solution to the zinc precursor solution of step (1), wherein the volume ratio of the precursor solution to the catalyst solution is 2:1, mixing well, and reacting at 60° C. for 24 hours;

[0052] (4) After the reaction is completed, the solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence, and dried under a nitrogen environment to obtain zinc nanowires with a conversion rate of about 70%.

[0053] Figure 3 This is a SEM image of zinc nanowires synthesized in Example 2. Figure 3 As shown, the synthesized product is mainly zinc nanowires with a diameter of about 30-180 nm and a length of about 5-20 μm. Compared with Example 1, using titanium tetrabromide as a catalyst, a higher yield can be obtained at a lower reaction temperature, but the synthesized zinc nanowires are accompanied by some irregular particles and uneven size distribution.

[0054] Example 3

[0055] ((1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0056] (2) dissolving titanium tetraiodide in n-hexane solution to prepare a catalyst solution with a concentration of 0.034 mol / L;

[0057] (3) adding the prepared catalyst solution to the zinc precursor solution of step (1), wherein the volume ratio of the precursor solution to the catalyst solution is 2:1, mixing well, and reacting at 90° C. for 48 hours;

[0058] (4) After the reaction is completed, the solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence and dried under a nitrogen environment to obtain zinc nanowires with a conversion rate of about 5%.

[0059] Figure 4 This is a SEM image of zinc nanowires synthesized in Example 3. Figure 4 As shown, the synthesized product is accompanied by irregular particles and a small amount of iodide, the nanowire diameter is about 50-120nm, and the length is about 5-30μm. Compared with Example 1, the conversion rate of zinc nanowires obtained by using titanium tetraiodide as a catalyst is lower, and the accompanying iodide is difficult to remove.

[0060] Example 4

[0061] (1) adding a n-hexane solution of diethyl zinc (1 mol / L) into a reaction vessel, and adding an equal volume of ether to adjust the concentration of diethyl zinc to 0.5 mol / L;

[0062] (2) dissolving titanium tetrachloride in ether solution to prepare a catalyst solution with a concentration of 0.034 mol / L;

[0063] (3) adding the prepared catalyst solution to the zinc precursor solution of step (1), wherein the volume ratio of the precursor solution to the catalyst solution is 2:1, mixing well, and reacting at 60° C. for 24 hours;

[0064] (4) After the reaction is completed, the solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence, and dried under a nitrogen environment to obtain zinc nanowires with a conversion rate of about 15%.

[0065] The test results show that the diameter of the zinc nanowires is 20-70 nm. Compared with the synthesis conditions of Example 1, the zinc nanowires synthesized under this condition have a smaller diameter and the conversion rate is reduced.

[0066] Example 5

[0067] (1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0068] (2) adding N,N-dimethyldecylamine to the above solution, wherein the volume ratio of N,N-dimethyldecylamine to diethylzinc in n-hexane solution is 1:10, and the concentration of N,N-dimethyldecylamine is about 0.4 mol / L;

[0069] (3) dissolving titanium tetrachloride in n-hexane solution to prepare a catalyst solution with a concentration of 0.034 mol / L;

[0070] (4) adding the prepared catalyst solution to the mixed solution of step (2), wherein the volume ratio of the precursor solution to the catalyst solution is 2:1, mixing well, and reacting at 135° C. for 48 hours;

[0071] (4) After the reaction is completed, the solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence, and dried under a nitrogen environment to obtain zinc nanowires. The diameter of the nanowires is mainly distributed in the range of 40-100 nm, and the conversion rate is about 15%.

[0072] Compared with Example 1, this reaction condition introduces dimethyldecylamine as a surfactant, and the size of the obtained nanowires is more uniform, but the conversion rate is slightly reduced.

[0073] Example 6

[0074] (1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0075] (2) Add octadecylamine to the above solution. The volume ratio of octadecylamine to diethylzinc in n-hexane solution is 1:10. At this time, the concentration of octadecylamine is about 0.28 mol / L.

[0076] (3) dissolving titanium tetrabromide in n-hexane solution to prepare a catalyst solution with a concentration of 0.034 mol / L;

[0077] (4) adding the prepared catalyst solution to the mixed solution of step (2), wherein the volume ratio of the precursor solution to the catalyst solution is 2:1, mixing well, and reacting at 150° C. for 24 hours;

[0078] (4) After the reaction, the solid product was washed with n-hexane, tetrahydrofuran, and isopropanol in sequence and dried under nitrogen to obtain zinc nanowires with a conversion rate of about 20%.

[0079] Figure 5 This is a SEM image of zinc nanowires synthesized in Example 6. Figure 5As shown in Figure 2, the length of the synthesized zinc nanowires is 10-20 μm, and the diameter is mainly 40-100 nm. Compared with the zinc nanowires synthesized in Example 2 (without using surfactant), the irregular particles in the synthesized product under this condition are reduced, and the morphology and size of the zinc nanowires are more uniform. The diameter statistics are shown in Figure 2. Figure 6 As shown in Figure 2, the diameter of the nanowires is mainly distributed in the range of 40-100 nm. Transmission electron microscopy images and selected area electron diffraction images are shown in Figure 2. Figure 7 As shown, by calibrating the selected area electron diffraction spots, it is determined that the synthesized nanowire has a single crystal structure and is a metal zinc single crystal nanowire.

[0080] Example 7

[0081] (1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0082] (2) Add octadecylamine to the above solution. The volume ratio of octadecylamine to diethylzinc in n-hexane solution is 1:10. At this time, the concentration of octadecylamine is about 0.28 mol / L.

[0083] (2) dissolving titanium tetrabromide in n-hexane solution to prepare a catalyst solution with a concentration of 0.017 mol / L;

[0084] (3) adding the prepared catalyst solution to the mixed solution of step (2) in a volume ratio of 2:1, mixing well, and reacting at 180° C. for 12 hours;

[0085] (4) After the reaction is completed, the solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence, and dried under a nitrogen environment to obtain zinc nanowires with a conversion rate of about 15%.

[0086] Figure 8 This is a SEM image of zinc nanowires synthesized in Example 7. Figure 8 As shown, the length of the zinc nanowire is 5-10 μm and the diameter is 20-70 nm. Compared with the synthesis conditions of Example 6, it is shown that under appropriate conditions, metal zinc nanowires with smaller diameters can be obtained by increasing the reaction temperature.

[0087] The experimental conditions in the above Examples 1-7 are summarized in the table below.

[0088]

[0089] Comparative Example 1

[0090] (1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0091] (2) Heating to 300°C, maintaining for 2 hours, with a heating rate of 5°C / min;

[0092] (3) The solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence, and dried under nitrogen to obtain the product metal zinc, the morphology of which is as follows: Fig. 9 As shown, relative to Examples 1-7, direct pyrolysis of diethyl zinc will yield zinc particles with irregular morphology.

[0093] Comparative Example 2

[0094] (1) adding a n-hexane solution of diethylzinc (1 mol / L) as a zinc precursor solution into a reaction vessel;

[0095] (2) Add octadecylamine to the above solution. The volume ratio of octadecylamine to diethylzinc in n-hexane solution is 1:2. At this time, the concentration of octadecylamine is about 1.4 mol / L.

[0096] (3) dissolving titanium tetrabromide in n-hexane solution to prepare a catalyst solution with a concentration of 0.034 mol / L;

[0097] (4) adding the prepared catalyst solution to the mixed solution of step (2), wherein the volume ratio of the precursor solution to the catalyst solution is 2:1, mixing well, and reacting at 150° C. for 24 hours;

[0098] (4) After the reaction is completed, the solid product is washed with n-hexane, tetrahydrofuran, and isopropanol in sequence, and dried under nitrogen to obtain zinc nanoparticles having the following morphology: Fig.10 shown.

[0099] Compared with Example 6, this comparative example increased the amount of surfactant used, but only irregular zinc nanoparticles were obtained.

Claims

1. A method for preparing zinc nanowires, comprising: (1) mixing a solvent, a zinc precursor and an optional surfactant to obtain a solution 1; (2) mixing the solvent and the catalyst to obtain solution 2; (3) mixing solutions 1 and 2 to obtain solution 3, and heating the solution to decompose the zinc precursor to obtain zinc nanowires; Wherein, the solvent is selected from C5-C7 alkanes, C5-C7 cycloalkanes and ether, The zinc precursor is denoted as ZnR 1 2, where R 1 independently selected from alkyl groups having 2 or more carbon atoms, The catalyst used is a titanium-based catalyst; the titanium-based catalyst is selected from TiR 2 4, where R 2 Independently selected from chlorine, bromine, iodine, cyclopentadienyl, C1-C6 alkoxy; The surfactant used is an amine-based surfactant.

2. The preparation method according to claim 1, wherein The solvent is n-hexane or a combination of n-hexane and ether.

3. The preparation method according to claim 1, wherein R 1 It is a C2-C10 alkyl group.

4. The preparation method according to claim 3, wherein R 1 It is a C2-C4 alkyl group.

5. The preparation method according to claim 1, wherein The zinc precursor is selected from diethylzinc, dipropylzinc and diisobutylzinc.

6. The preparation method according to claim 1, wherein The titanium-based catalyst is selected from one or a combination of two or more of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, bis(cyclopentadienyl)titanium dichloride, cyclopentadienyltitanium trichloride, titanium tetraisopropoxide, titanium acetylacetonate, and tetrabutyl titanate.

7. The preparation method according to claim 1, wherein The amine-based surfactant is represented by R 3 N(CH3)2, where R 3 Selected from C4-C20 alkyl.

8. The preparation method according to claim 7, wherein: The amine-based surfactant is selected from one or a combination of two or more of octadecylamine, hexadecylamine, dodecylamine, N,N-dimethyldecylamine and N,N-dimethylhexylamine.

9. The preparation method according to any one of claims 1 to 8, wherein: In solution 3, the concentration of the zinc precursor is 0.2-2 mol / L, in terms of molar concentration of zinc.

10. The preparation method according to claim 9, wherein The concentration of the zinc precursor is 0.2-1.5 mol / L, measured as the molar concentration of zinc.

11. The preparation method according to any one of claims 1 to 8, wherein: In solution 3, the concentration of the catalyst is 0.001-0.1 mol / L, calculated as the molar concentration of titanium.

12. The preparation method according to claim 11, wherein The concentration of the catalyst is 0.003-0.05 mol / L, calculated as the molar concentration of titanium.

13. The preparation method according to any one of claims 1 to 8, wherein: In solution 3, the concentration of the surfactant is 0-0.5 mol / L.

14. The preparation method according to claim 13, wherein: The concentration of the surfactant is 0.1-0.4 mol / L.

15. The preparation method according to any one of claims 1 to 8, wherein: In step (3), the molar ratio of zinc precursor to catalyst is 30-200:

1.

16. The preparation method according to claim 15, wherein: The molar ratio of zinc precursor to catalyst is 60-120:

1.

17. The preparation method according to any one of claims 1 to 8, wherein: In step (3), the reaction temperature for the decomposition reaction is 60-200°C.

18. The preparation method according to claim 17, wherein: The reaction temperature for the decomposition reaction is 60-150°C.

19. The preparation method according to any one of claims 1 to 8, further comprising a purification step: filtering the reaction product to obtain a precipitated product, which is then washed and dried.

20. The preparation method according to claim 19, wherein: The washing is carried out with a solvent, and the solvent is one or a combination of two or more of hexane, toluene, tetrahydrofuran, 1,4-dioxane, and isopropanol; Drying was carried out under nitrogen atmosphere.

21. A zinc nanowire prepared by the preparation method according to any one of claims 1 to 20.

Citation Information

Patent Citations

  • Solvothermal controlled preparation method for ZnMnS nanowire

    CN102633305A

  • Method of catalytic preparation of copper-indium-tellurium nanowires

    CN104057101A